Bhinneka tunggal ika: the urgency of building character education in maintaining unity - Ahmad Mufid; Dadang Sundawa (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
Character education is part of the solution to improving the quality of national education implementation. In the character crisis, which is decreasing every year, it is feared that it will threaten the nation's character and culture, especially in this era of increasingly massive globalization. The presence of globalization can no longer be stopped, so every country in its role and function must be balanced in adopting policies that can prevent the emergence of values that can damage national unity and integrity. In accordance with the nation's motto, Bhinneka Tunggal Ika is present in the call to realize complete togetherness. The country of Indonesia consists of various tribes, religions, races, religions, and tribes. Everything is the essence of God Almighty which is worthy of gratitude. Considering the many differences, a unifying symbol is needed so that it is not easily divided. Regarding character education, strategic steps need to be taken to participate in resolving conflicts that can divide unity and integrity. Character education is an alternative form of prevention because it basically has the aim of building, indoctrinating, and educating a better future generation. The method used in this research is a literature study with a focus on references that are relevant to current problems. Character education in the context of unity in diversity, which makes the country's elements heterogeneous, starting from ethnicity, religion, race, and religion, is certainly relevant in instilling character in accordance with the motto of the Indonesian nation.